Characterization of Borrelia burgdorferi BlyA and BlyB Proteins: a Prophage-Encoded Holin-Like System - Damman, Christopher J. (American Society for Microbiology, 2000)
The conserved cp32 plasmid family of Borrelia burgdorferi was recently shown to be packaged into a bacteriophage particle (C. H. Eggers and D. S. Samuels, J. Bacteriol. 181:7308–7313, 1999). This plasmid encodes BlyA, a 7.4-kDa membrane-interactive protein, and BlyB, an accessory protein, which were previously proposed to comprise a hemolysis system. Our genetic and biochemical evidence suggests that this hypothesis is incorrect and that BlyA and BlyB function instead as a prophage-encoded holin or holin-like system for this newly described bacteriophage. An Escherichia coli mutant containing the blyAB locus that was defective for the normally cryptic host hemolysin SheA was found to be nonhemolytic, suggesting that induction of sheA by blyAB expression was responsible for the hemolytic activity observed previously. Analysis of the structural features of BlyA indicated greater structural similarity to bacteriophage-encoded holins than to hemolysins. Consistent with holin characteristics, subcellular localization studies with E. coli and B. burgdorferi indicated that BlyA is solely membrane associated and that BlyB is a soluble protein. Furthermore, BlyA exhibited a holin-like function by promoting the endolysin-dependent lysis of an induced lambda lysogen that was defective in the holin gene. Finally, induction of the cp32 prophage in B. burgdorferi dramatically stimulated blyAB expression. Our results provide the first evidence of a prophage-encoded holin within Borrelia.